Characterization of hexamethyldisiloxane plasma polymerization in a DC glow discharge in an argon flow - Zuza, Daniil A.; Nekhoroshev, Vitaly O.; Batrakov, Alexander V.; Markov, Alexey B.; Kurzina, Irina A. (Vacuum)
This work aims to study hexamethyldisiloxane (HMDSO) plasma polymerization in a low-pressure glow discharge in a gas flow. HMDSO was activated in a plasma-chemical reactor with a DC glow discharge in an argon flow. The argon flow (the mass flow rate was 230 mg/min) was injected in the direction of the anode from the cathode. HMDSO vapors were injected into the plasma-chemical reactor either through the hollow cathode or through the inlet located between the cathode and the anode. Polymer coatings were deposited on the substrates located in a vacuum chamber. Plasma polymerization was characterized based on the mass of coatings deposited under varying external conditions: the HMDSO mass flow rate (1–10 mg/min), the average discharge current (6–60 mA), and the discharge power (6–30 W). The operation modes of the plasma-chemical system were determined. The chemical structure of the coatings was analyzed using the infrared spectroscopy. The processes occurring in different regions of the glow discharge and at the interface near the substrate surface are proposed. A DC glow discharge in a gas flow can be used for local deposition of polymer coatings on the surface of dielectric or conductive materials.